Apolipoprotein J is a hepatokine regulating muscle glucose metabolism and insulin sensitivity - Seo, Ji A. (2020)
Funding Information: This work was supported by grants from the National Institutes of Health (R01DK111529 and R01DK106076 to Y.-B.K.) and in part by Merit Review Award (I01CX00635) from the United States Department of Veterans Affairs Clinical Sciences Research and Development Service (R.R.H.), grants from the Basic Science Research Program through the National Research Foundation of Korea (NRF) funded by the Ministry of Education (2018R1D1A1B07049123 to J.A.S. and 2017R1A6A3A03003298 to W.-M.Y.), a grant from the Korean Diabetes Association (2017S-2 to J.A.S.), and a grant from Korea University (K1813091 to J.A.S.). The contents do not represent the views of the U.S. Department of Veterans Affairs or the United States Government. The Animal Metabolic Physiology Core (P30 DK057521 Barbara Kahn) performed in vivo glucose uptake. M.-C.K. is a recipient of a postdoctoral fellowship award from the American Diabetes Association (1-17-PDF-146), I.S.L. is a recipient of FCT fellowship from Portugal (SFRH/BD/71021/2010), and L.P.M is a recipient of São Paulo Research Foundation from Brazil (FAPESP 2013/ 14149-6). We would like to thank Barbara Kahn, Tony Hollenberg, and Terry Flier for helpful discussions, Odile Peroni for technical assistance on in vivo glucose uptake, Amira Klip for the C2C12-myc-Glut4 cell line, Sungman Cho for glucose uptake assays, Jin Sung Park for VLDL-secretion, Wendy Li for Immunofluorescent analysis, Zoltan Arany for myogenin-Cre transgenic mice, Inkyu Lee for ApoJ adenovirus, and Min Bon Hong for ApoJ recombinant protein. Publisher Copyright: © 2020, The Author(s).